The inclusion toolkit - Herbert, Sarah (SAGE, 2011)
The practical strategies suggested in this book are supported by current research into effective teaching and learning, and show you how inclusion friendly teaching could look in your classroom. Rather than focusing on the differences between learners, the common strategies that will enhance the learning of all, based on the common concerns of class teachers working with pupils who have special educational needs, are identified.--[book cover]